Digital Governance Model for Village-Owned Enterprise Financial Accountability in Bengkalis - Muhammad Fadhil Junery; Siti Naaishah Hambali; Hainnur Aqma Rahim (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2026)
Purpose – This article develops a strategic model for strengthening financial accountability in village-owned enterprises (BUMDes) in Bengkalis Regency, Indonesia, by prioritizing governance reform strategies using an integrated qualitative and multi-criteria decision framework. Method – The study builds on qualitative evidence that formal BUMDes structures exist but remain weak in planning, reporting, supervision, human-resource competence, and community oversight. To move beyond descriptive diagnosis, the study integrates thematic findings with Analytic Network Process and Benefit, Opportunity, Cost, Risk (ANP-BOCR) analysis. Data were obtained through interviews, expert judgment, documents, and field observation involving BUMDes directors and governance experts. Findings – The model identifies four strategic alternatives: digital governance, strengthened supervision, human-resource capacity building, and institutional collaboration. The ANP-BOCR synthesis ranks digital governance as the strongest strategic priority (0.466), followed by supervision (0.277), capacity building (0.160), and collaboration (0.097). The article concludes that digitalisation should be positioned as an integrated accountability infrastructure rather than a narrow software intervention. Implications – Effective implementation requires digital reporting, control procedures, managerial training, and inter-institutional support. The findings provide valuable implications for BUMDes managers, village governments, and other relevant policymakers, including the Bengkalis Regency Government, in strengthening the governance and financial management of BUMDes.